At Westonci.ca, we make it easy to get the answers you need from a community of informed and experienced contributors. Join our Q&A platform to get precise answers from experts in diverse fields and enhance your understanding. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.

use the two given functions to write y as a function of x

y=3m-5, m=x+5/3


Sagot :

y=3x

Step-by-step explanation:

y=3x-5

but

m=x+5/3

replace m in 3m to 3(x +5/3)

i.e

y=3(x+5/3)-5

y=3x +5-5

y=3x